Combining stereo‐video monitoring and physiological trials to estimate reef fish metabolic demands in the wild. Issue 7 (5th July 2022) - Schiettekatte, Nina M. D.; Conte, Francesca; French, Beverly; Brandl, Simon J.; Fulton, Christopher J.; Mercière, Alexandre; Norin, Tommy; Villéger, Sébastien; Parravicini, Valeriano
Abstract: Organismal metabolic rates (MRs) are the basis of energy and nutrient fluxes through ecosystems. In the marine realm, fishes are some of the most prominent consumers. However, their metabolic demand in the wild (field MR [FMR]) is poorly documented, because it is challenging to measure directly. Here, we introduce a novel approach to estimating the component of FMR associated with voluntary activity (i.e., the field active MR [ AM R field ] ). Our approach combines laboratory‐based respirometry, swimming speeds, and field‐based stereo‐video systems to estimate the activity of individuals. We exemplify our approach by focusing on six coral reef fish species, for which we quantified standard MR and maximum MR (SMR and MMR, respectively) in the laboratory, and body sizes and swimming speeds in the field. Based on the relationships between MR, body size, and swimming speeds, we estimate that the activity scope (i.e., the ratio between AM R field and SMR) varies from 1.2 to 3.2 across species and body sizes. Furthermore, we illustrate that the scaling exponent for AM R field varies across species and can substantially exceed the widely assumed value of 0.75 for SMR. Finally, by scaling organismal AM R field estimates to the assemblage level, we show the potential effect of this variability on community metabolic demand. Our approach may improve our ability to estimate elemental fluxes mediated by a critically important group of aquatic animals through a non‐destructive, widely applicable technique. Abstract : We know little about the metabolic demand of fishes in the wild. We propose a new approach to estimate active field metabolic rates by combining laboratory‐based respirometry and field‐based stereo‐video systems.